Synthesis and Application of New Ruthenium Complexes Containing β-Diketonato Ligands as Sensitizers for Nanocrystalline TiO2 Solar Cells - Ashraful Islam; Surya Prakash Singh; Liyuan Han (International Journal of Photoenergy)
Five heteroleptic ruthenium complexes having different β-diketonato ligands, [Ru(tctpy)(dppd)(NCS)] (1), [Ru(tctpy)(pd)(NCS)] (2), [Ru(tctpy)(tdd)(NCS)] (3), [Ru(tctpy)(mepd)(NCS)] (4), and [Ru(tctpy)(tmhd)(NCS)] (5), where tctpy = 4,4′,4′′-tricarboxy-2,2′:6′,2′′-terpyridine, pd = pentane-2,4-dione, mepd = 3-methylpentane-2,4-dione, tmhd = 2,2,6,6-tetramethylheptane-3,5-dione, tdd = tridecane-6,8-dione, and dppd = 1,3-diphenylpropane-1,3-dione, were synthesized and characterized. These heteroleptic complexes exhibit a broad metal-to-ligand charge transfer absorption band over the whole visible range extending up to 950 nm. The low-energy absorption bands and the E (Ru3+/2+) oxidation potentials in these complexes could be tuned to about 15 nm and 110 mV, respectively, by choosing appropriate β-diketonate ligands. Molecular orbital calculation of complex 1 shows that the HOMO is localized on the NCS ligand and the LUMO is localized on the tctpy ligand, which is anchored to the TiO2 nanoparticles. The β-diketonato-ruthenium(II)-polypyridyl sensitizers, when anchored to nanocrystalline TiO2 films for light to electrical energy conversion in regenerative photoelectrochemical cells, achieve efficient sensitization to TiO2 electrodes with increasing activity in the order 5 < 4 < 3 ≈ 2 < 1. Under standard AM 1.5 sunlight, the complex 1 yielded a short-circuit photocurrent density of 16.7 mA/cm2, an open-circuit voltage of 0.58 V, and a fill factor of 0.64, corresponding to an overall conversion efficiency of 6.2%. A systematic tuning of HOMO energy level shows that an efficient sensitizer should possess a ground-state redox potential value of >+.53 V versus SCE.